General Principals of miRNA Biogenesis and Regulation in the Brain - O'Carroll, Dónal (Nature Publishing Group, 2013)
MicroRNAs (miRNAs) are small, noncoding RNAs that mediate posttranscriptional gene suppression in a sequence-specific manner. The ability of a single miRNA species to target multiple messenger RNAs (mRNAs) makes miRNAs exceptionally important regulators of various cellular functions. The regulatory capacity of miRNAs is increased further by the miRNA ability to suppress gene expression using multiple mechanisms that range from translational inhibition to mRNA degradation. The high miRNA diversity multiplied by the large number of individual miRNA targets generates a vast regulatory RNA network than enables flexible control of mRNA expression. The gene-regulatory capacity and diversity of miRNAs is particularly valuable in the brain, where functional specialization of neurons and persistent flow of information requires constant neuronal adaptation to environmental cues. In this review we will summarize the current knowledge about miRNA biogenesis and miRNA expression regulation with a focus on the role of miRNAs in the mammalian nervous system.